Antithrombotic treatment and intracerebral haemorrhage: between Scylla and Charybdis. Issue 4 (28th April 2015) - Hofmeijer, J; Kappelle, L J; Klijn, C J M
Abstract : In patients who have intracerebral haemorrhage while on antithrombotic treatment, there is no evidence from randomised clinical trials to support decisions with regard to antithrombotic medication. In the acute phase, we advise stopping all antithrombotic treatment with rapid reversal of antithrombotic effects of oral anticoagulants. After the acute phase, we discourage restarting oral anticoagulants in patients with a lobar haematoma caused by cerebral amyloid angiopathy because of the high risk of recurrent bleeding. In these patients, even treatment with platelet inhibitors needs careful weighing of the risks of bleeding and ischaemic stroke. In patients with non-lobar intracerebral haemorrhage, we suggest considering restarting optimal antithrombotic treatment. This includes treatment with oral anticoagulants for patients with atrial fibrillation and/or mechanical valve prosthesis. After intracerebral haemorrhage during oral anticoagulant therapy in patients with atrial fibrillation, direct anticoagulants may be better than vitamin K antagonists, but we await confirmation of this from ongoing trials.